Protection of the reputation of the Polish Nation and the Republic of Poland - Skrzypczak, Jędrzej (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
A pretext for taking up this topic was the adoption in January 2018 of the new Act of the Institute of National Remembrance, which aroused huge controversy. In this way, provisions were enacted to protect the reputation of the Republic of Poland and the Polish Nation. Among them, there are regulations such art. 53o and 53p providing civil liability for violating the reputation of the Republic of Poland and the Polish Nation. This part of the bill passed almost unnoticed, unlike the criminal law in this bill. Certainly, a full analysis of this normative act requires more time. For now, we can say that – as it was presented in this paper – the adopted regulation raises a number of doubts and questions about its proper interpretation.

Pretekstem do podjęcia tej problematyki ochrony dobrego imienia Narodu Polskiego i Rzeczypospolitej Polskiej było uchwalenie w styczniu 2018 r. wzbudzającej ogromne kontrowersje ustawy o zmianie ustawy o Instytucie Pamięci Narodowej. W ten sposób wprowadzono przepisy przewidujące ochronę dobrego imienia Rzeczypospolitej Polskiej i Narodu Polskiego. Pośród nich zaproponowano przepisy art. 53o i 53p przewidujące odpowiedzialność cywilnoprawną. Ten fragment ustawy przeszedł właściwie niezauważony, inaczej niż wzbudzające ogromne emocje przepisy przewidujące odpowiedzialność karną. Z pewnością pełna analiza tego aktu normatywnego wymaga znacznie dłuższego czasu. Jak wyżej próbowano wykazać, przyjęta regulacja rodzi szereg wątpliwości i pytań o jej właściwą wykładnię. Pomija w zasadzie całkowicie dorobek judykatury, który w poprzednim stanie prawnym pozwalał członkowi określonej grupy np. Narodu Polskiego dochodzenia roszczeń w przypadku naruszenia poczucia godności narodowej.
Ochrona dobrego imienia Narodu Polskiego i Rzeczypospolitej Polskiej
Keywords: protection of the reputation of the Polish Nation and the Republic of Poland; ochrona dobrego imienia Narodu Polskiego i Rzeczypospolitej Polskiej